Housing for People of All Ages : flexible, unrestricted, senior-friendly - Ebner, Peter; Feddersen, Eckhard; Giessler, Joachim; Lüdtke, Insa; Marx, Lothar; Schittich, Christian (in DETAIL, 2013)
Communal living, intergenerational living, living for families, handicap-accessible living, living and working, living and leisure time - the wide variety of current demands is shaping future concepts in housing, which will have to do justice to the needs of our increasingly multilayered society. The examples in this new volume in the In Detail series are correspondingly diverse. From the demand for stroller- and wheelchairaccessible housing through facilities that accommodate the needs of senior citizens all the way to the modernization of existing buildings, the selection of projects offers a panoramic overview. Organized thematically, In Detail: Integrated Housing highlights a variety of well-defined topics, such as handicap-accessibility and flexibility of use, and presents them together with explanatory technical articles and examples of realized projects. In closing, it provides addresses of information centers and associations as well as sources of additional information. Gemeinschaftliches Wohnen, generationenübergreifendes Wohnen, Wohnen für Familien, barrierefreies Wohnen, Wohnen und Arbeiten, Wohnen und Freizeitgestaltung - die Vielfalt der Anforderungen bestimmt zukünftige Wohnkonzepte, die den Ansprüchen und Bedürfnissen unserer immer vielschichtigeren Gesellschaft gerecht werden sollen. Ebenso breit gefächert sind daher auch die Beispiele in diesem neuen Band der Reihe im Detail. Von Wohnanlagen für Kinderwagen und Rollstuhl, über eine seniorengerechte Ausstattung bis hin zur Modernisierung bestehender Bauten bietet die Projektauswahl einen umfassenden Überblick. Thematisch gegliedert werden in "im Detail: Integriertes Wohnen" gezielt einzelne Schwerpunkte, wie zum Beispiel Barrierefreiheit oder Nutzungsflexibilität sowohl mit erläuternden Fachartikeln als auch anhand der realisierten Projekte mit großmaßstäblichen Konstruktionszeichnungen vorgestellt. Ergänzend bietet der Band Adressen zu Beratungsstellen und Verbänden sowie zu weiterführenden Fachinformationen.